Effects of a heat-stable yeast product and antibiotics in diets for nursery pigs - C L Jones; C W Starkey; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 192 pigs (average initial BW of 15 lb and 21 d of age) were used in a 35-d experiment to determine the effects of a heatstable yeast product on growth performance of nursery pigs fed diets without and with antibiotics. Treatment diets were formulated to: 1.7% lysine for d 0 to 7, 1.5% lysine for d 7 to 21, and 1.3% lysine for d 21 to 35. The treatments were arranged as a 2 × 2 factorial, with main effects of antibiotics (without and with carbadox at 50 g/ton) and yeast (without and with 0.2% Biosaf). All diets had 3,000 ppm total Zn for d 0 to 7 and 250 ppm total Cu for d 7 to 35. For d 0 to 7 and 7 to 21, the diets were steam conditioned for approximately 10 seconds at atmospheric pressure and temperatures of 140oF and 160oF, respectively. For d 21 to 35, the diets were fed in meal form. The antibiotic improved efficiency of gain for d 0 to 7 and 0 to 21 (P0.15) and there were no interactions among antibiotic and yeast addition in any phase of the experiment (P>0.08). In conclusion, the antibiotic (carbadox) was effective as a non-specific growth promoter, but the yeast product had minimal effect.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Nursery; Antibiotic; Yeast; Swine